192k views
5 votes
How do you find this?

How do you find this?-example-1
User MegaBytes
by
5.0k points

1 Answer

6 votes

Answer:

g' (- 2) =
(1)/(2)

Explanation:

let y = g(x) and rearrange making x the subject, that is

y =
(2)/(1-4x) ( multiply both sides by 1 - 4x )

y(1 - 4x) = 2 ← distribute left side

y - 4xy = 2 ( subtract y from both sides )

- 4xy = 2 - y ( multiply through by - 1 )

4xy = y - 2 ( divide both sides by 4y )

x =
(y-2)/(4y)

change y back into terms of x with x = g'(x)

g'(x) =
(x-2)/(4x) , then

g'(- 2) =
(-2-2)/(4(-2)) =
(-4)/(-8) =
(1)/(2)

User Nadeem Jamali
by
5.3k points